Deposits as Currency - Dunbar, Charles F. (Quarterly Journal of Economics, 1887)
Deposits as Currency Get access Charles F. Dunbar Charles F. Dunbar Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 1, Issue 4, July 1887, Pages 401–419, https://doi.org/10.2307/1879338 Published: 01 July 1887